Application of Nano Copper Alloy Particles in Aging Wine
By using modified concave and convex rod soil, sodium alginate and hydroxypropyl trimethylammonium chloride chitosan, the problem of poor aging of new wine was solved, and the fragrance and taste of new wine was improved and the increase of ester and aroma components were increased.
Patent Information
- Application Number
- CN202410724682.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-05
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-06-05
AI Technical Summary
The existing technology is difficult to effectively urge new wine to be aged, resulting in the spicy and bad smell of new wine being difficult to eliminate, and the aroma components are not complex enough, which affects the quality of the wine.
Nanocopper alloy particles were used to treat modified concave and convex rod soil with sodium alginate and hydroxypropyl trimethylammonium chloride chitosan. After calcination and ball milling, nanocopper alloy particles were obtained, which were used to treat new wine to promote their aging.
Significantly increase the aroma and taste of the new wine, increase the ester content in the wine, reduce the acetaldehyde and acetal content in the wine, improve the aroma and taste of the wine, and improve the quality of the wine.
Smart Images

Figure BDA0004878244710000121 
Figure BDA0004878244710000131
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of aging of new wine, and in particular to the application of nano copper alloy particles in aging wine. Background Art
[0002] Newly distilled liquor is spicy but not mellow, with a strong irritating alcohol taste and a sense of rush, which makes people feel uncomfortable after drinking. Aging is an important process in the production of distilled liquor. The aging of traditional distilled liquor is to store the raw liquor under natural conditions for a sufficient period of time, so that various substances in the distilled liquor can complete complex physical and chemical changes, eliminate the spicy taste and bad smell of the new liquor, and produce more aroma and flavor substances, making the aroma components of the liquor more complex and rich, the taste of the liquor becomes coordinated and soft, the sensory quality of the liquor is significantly improved, and it shows a typical aroma and style.
[0003] The artificial method of accelerating the aging of wine is called accelerated aging. The main reactions in the accelerated aging process are oxidation and esterification. The purpose of accelerated aging is to select appropriate physical or chemical methods to destroy the hydrogen bonds between ethanol molecules, destroy self-association, accelerate the activation of water molecules and ethanol molecules, and then depolymerize into single molecules. The second purpose of accelerated aging is to find ways to make the depolymerized single molecules re-associate and undergo biochemical reactions with each other to generate new substances, which play an important role in improving the quality of wine. When accelerating aging, external energy is an important condition. It is reported that hydrogen bond association is not a controlling factor in the aging of distilled wine. The chemical changes in the wine body after aging, which lead to the increase of the main aroma component-esters, become the main factor controlling the aging process.
[0004] The current methods for aging new wine include nanotechnology, potassium permanganate oxidation, metal ion catalysis, oxygen aging, molecular sieve ripening, magnetic field treatment, etc.; and the aging effects of new wine obtained by different processes vary greatly.
[0005] Therefore, developing a process for effectively accelerating the aging of new wine is one of the technical problems that need to be solved at present, and it has good application prospects. Summary of the invention
[0006] The present invention is based on solving the above technical problems, and thus provides the technology of the present invention. The technical solution of the present invention includes the application of nano copper alloy particles in aging wine.
[0007] The invention uses attapulgite to be treated with hydrogen peroxide and hydrochloric acid, and then calcined to obtain modified attapulgite; then the nano copper-zinc alloy is treated with sodium alginate and hydroxypropyltrimethylammonium chloride chitosan, and then calcined to obtain nano copper alloy particles. The particles have a good aging and mellowing effect on new liquor, can significantly increase the aroma and taste of the new liquor, and can increase the ester content in the liquor and reduce the acetaldehyde content in the liquor.
[0008] The present invention provides application of nano copper alloy particles in aged wine, wherein the nano copper alloy particles include nano copper-zinc alloy particles, and the preparation method of the nano copper alloy particles includes:
[0009] Step 1: adding sodium alginate, hydroxypropyltrimethylammonium chloride chitosan, nano copper-zinc alloy, modified attapulgite and water into a container, heating and stirring to obtain a mixture;
[0010] Step 2: Filter, calcine, ball-mill and sieve the filtered solid material to obtain intermediate material particles;
[0011] Step 3: Mix the intermediate material particles and potassium permanganate to obtain the nano copper alloy particles.
[0012] Furthermore, in step 1, the mass ratio of sodium alginate to hydroxypropyltrimethylammonium chloride chitosan is 0.5-1:1.
[0013] Furthermore, in step 1, the mass ratio of water to modified attapulgite is 10-50:1.
[0014] Furthermore, in step 1, the mass ratio of the total mass of sodium alginate and hydroxypropyltrimethylammonium chloride chitosan to the nano copper-zinc alloy is 1-2:1.
[0015] Furthermore, in step 1, the mass ratio of modified attapulgite to nano copper-zinc alloy is 10-100:1.
[0016] Furthermore, in step 1, the temperature is heated to 40-75°C.
[0017] Furthermore, in step 1, the stirring speed is 50-500 rpm.
[0018] Furthermore, in step 1, the stirring time is 4-12 hours.
[0019] Furthermore, in step 2, the filtration is performed using a nanofiltration membrane having a pore size of about 2 nanometers.
[0020] Furthermore, in step 2, the calcination temperature is 700-850° C. and the calcination time is 1.5-3 hours.
[0021] Furthermore, in step 2, the particle size selected by sieving is between 1 and 500 microns.
[0022] Furthermore, in step 3, the mass ratio of the intermediate material particles to potassium permanganate is 10-100:1.
[0023] Furthermore, in step 3, the particle size of potassium permanganate is between 1 and 500 microns.
[0024] Furthermore, the preparation method of the nano copper alloy particles comprises:
[0025] Step 1: adding sodium alginate, hydroxypropyltrimethylammonium chloride chitosan, nano copper-zinc alloy, modified attapulgite and water into a container, heating to 40-75° C. and stirring at 50-500 rpm for 4-12 hours to obtain a mixture;
[0026] The mass ratio of sodium alginate and hydroxypropyltrimethylammonium chloride chitosan is 0.5-1:1, the mass ratio of water to modified attapulgite is 10-50:1, the mass ratio of the total mass of sodium alginate and hydroxypropyltrimethylammonium chloride chitosan to the nano-copper-zinc alloy is 1-2:1, and the mass ratio of modified attapulgite to the nano-copper-zinc alloy is 10-100:1;
[0027] Step 2: Filter, calcine the filtered solid material at 700-850°C for 1.5-3 hours, ball mill and sieve to select particles with a particle size between 1-500 microns to obtain intermediate material particles;
[0028] Step 3: Mix the intermediate material particles and potassium permanganate with a particle size of 1-500 microns at a mass ratio of 10-100:1 to obtain the nano copper alloy particles.
[0029] Furthermore, the preparation method of the modified attapulgite comprises:
[0030] S1: stirring attapulgite with water, acid solution and hydrogen peroxide to obtain a stirred material;
[0031] S2: stirring the material and filtering it, filtering the solids, calcining, grinding and screening them to obtain the modified attapulgite.
[0032] Furthermore, in S1, the attapulgite is food grade attapulgite, and the attapulgite is particles with a particle size of 5-500 microns.
[0033] Furthermore, in S1, the acid solution is a hydrochloric acid solution with a mass concentration of 20-30wt%.
[0034] Furthermore, in S1, the concentration of hydrogen peroxide is 5-10wt%.
[0035] Furthermore, in S1, the mass ratio of attapulgite to water is 1:20-100.
[0036] Furthermore, in S1, the mass ratio of attapulgite to acid solution is 1:0.4-2.
[0037] Furthermore, in S1, the mass ratio of attapulgite to hydrogen peroxide is 1:0.2-1.
[0038] Furthermore, in S1, the stirring speed is 40-600 rpm and the stirring time is 2-6 hours.
[0039] Furthermore, in said S1, the filter pore size is 0.1-2 microns.
[0040] Furthermore, in S2, the calcination temperature is 800-950° C. and the calcination time is 1-3 hours.
[0041] Furthermore, in S2, particles with a particle size between 2 and 400 microns are selected by screening.
[0042] Furthermore, the preparation method of the modified attapulgite comprises:
[0043] S1: stirring attapulgite with water, a hydrochloric acid solution with a concentration of 20-30wt%, and a hydrogen peroxide solution with a concentration of 5-10wt% for 2-6 hours to obtain a stirred material; wherein the mass ratio of attapulgite to water is 1:20-100, the mass ratio of attapulgite to hydrochloric acid solution is 1:0.4-2, and the mass ratio of attapulgite to hydrogen peroxide is 1:0.2-1;
[0044] S2: The stirred material is filtered through a pore size of 0.1-2 microns, the filtered solids are calcined at 800-950° C. for 1-3 hours, ground and sieved to select particles between 2-400 microns, and the modified attapulgite is obtained.
[0045] Furthermore, the application also includes the steps of mixing the nano copper alloy particles with the newly prepared wine and then filtering with a nano membrane.
[0046] Beneficial effects:
[0047] The invention uses attapulgite to be treated with hydrogen peroxide and hydrochloric acid, and then calcined to obtain modified attapulgite; then the modified attapulgite is treated with sodium alginate and hydroxypropyltrimethylammonium chloride chitosan to obtain nano copper-zinc alloy, and then calcined to obtain nano copper alloy particles. The particles are used to treat newly produced liquor, and have a good aging and alcoholization effect on the newly produced liquor.
[0048] After the nano copper alloy particles of the present invention are used to treat new liquor, the acetaldehyde content can be reduced by 31.25%, making the liquor more beneficial to human health and reducing the adverse taste caused by acetaldehyde to a large extent.
[0049] After the nano copper alloy particles of the present invention are used to treat new wine, the proportion of acetal content can be reduced to as low as 4.82%.
[0050] After the nano copper alloy particles of the present invention are used to treat new wine, the contents of ethyl acetate and ethyl lactate can be increased, and the increase ratios reach 8.34% and 11.27% respectively.
[0051] In the preparation system of the present invention, the combination of sodium alginate and hydroxypropyltrimethylammonium chloride chitosan has a better effect on the prepared particles than using only one of them, and the two have a mutually reinforcing relationship in promoting the aging effect of new wine. When the ratio of the two is in the range of 0.5-1:1, the aging effect of wine is better.
[0052] In the preparation of modified attapulgite, the use of hydrogen peroxide and hydrochloric acid solution can increase the treatment effect of the particles on new wine, increase the taste of the wine and reduce the content of unfavorable components. In the present invention, the combination of a hydrochloric acid solution with a concentration of 20-30wt% and a hydrogen peroxide with a concentration of 5-10wt% can synergistically promote the effect of the particles on the treatment of new wine, increase the content of esters in the wine and reduce the content of acetaldehyde, and improve the aroma of the wine. The effect of low-concentration hydrochloric acid solution and hydrogen peroxide is much worse than the effect of the particles obtained by treating attapulgite with a hydrochloric acid solution with a concentration of 20-30wt% and a hydrogen peroxide with a concentration of 5-10wt%. DETAILED DESCRIPTION
[0053] The present invention will be described below in conjunction with specific embodiments, and various effects of the present invention will be more clearly presented. It should be understood by those skilled in the art that these specific embodiments are used to illustrate the present invention, rather than to limit the present invention.
[0054] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0055] 1. Preparation of modified attapulgite
[0056] Modified attapulgite 1: The preparation steps are as follows:
[0057] S1: Stir food-grade attapulgite with a particle size of 5-500 μm (Shandong Yichen Biotechnology Co., Ltd.) with deionized water, a 25 wt% hydrochloric acid solution, and an 8 wt% hydrogen peroxide solution at 60 rpm for 4 hours at room temperature to obtain a stirred material; wherein the mass ratio of attapulgite to water is 1:50, the mass ratio of attapulgite to hydrochloric acid solution is 1:0.8, and the mass ratio of attapulgite to hydrogen peroxide is 1:0.5;
[0058] S2: The stirred material is filtered through a 1 micron pore size, the filtered solid is calcined at 850° C. for 2 hours, ground and sieved to select particles between 10 and 100 microns, and the modified attapulgite 1 is obtained.
[0059] Modified attapulgite 2: The preparation steps are as follows:
[0060] S1: Stirring food-grade attapulgite with a particle size of 5-500 μm (Shandong Yichen Biotechnology Co., Ltd.) with deionized water, a 30 wt% hydrochloric acid solution, and a 7.2 wt% hydrogen peroxide solution at 60 rpm for 4 hours at room temperature to obtain a stirred material; wherein the mass ratio of attapulgite to water is 1:55, the mass ratio of attapulgite to hydrochloric acid solution is 1:1, and the mass ratio of attapulgite to hydrogen peroxide is 1:0.45;
[0061] S2: The stirred material is filtered through a 1 micron pore size, the filtered solid is calcined at 850° C. for 2.2 hours, ground and sieved to select particles between 10 and 100 microns, and the modified attapulgite 2 is obtained.
[0062] Modified attapulgite 3: Step S1: Stir food-grade attapulgite with a particle size of 5-500 μm (Shandong Yichen Biotechnology Co., Ltd.) with deionized water and a 25 wt% hydrochloric acid solution at 60 rpm for 4 hours at room temperature to obtain a stirred material; wherein the mass ratio of attapulgite to water is 1:50, and the mass ratio of attapulgite to hydrochloric acid solution is 1:1.3 ; Others are the same as those of modified attapulgite 1.
[0063] Modified attapulgite 4: S1: Food-grade attapulgite with a particle size of 5-500 μm (Shandong Yichen Biotechnology Co., Ltd.) was stirred with deionized water and 8 wt% hydrogen peroxide at 60 rpm at room temperature for 4 hours to obtain a stirred material; wherein the mass ratio of attapulgite to water was 1:50, and the mass ratio of attapulgite to hydrogen peroxide was 1:1.3 ; Others are the same as those of modified attapulgite 1.
[0064] Modified attapulgite 5: The concentration of the hydrochloric acid solution is 5 wt %, and the others are the same as those of modified attapulgite 1.
[0065] Modified attapulgite 6: The concentration of hydrogen peroxide is 2 wt %, and the rest are the same as those of modified attapulgite 1.
[0066] 2. Preparation of Nano Copper Alloy Particles
[0067] The nano copper-zinc alloy used in the preparation of the following nano copper alloy particles is a product of Shanghai Chaowei Nanotechnology Co., Ltd. with model CW-Cu-Zn, with an average particle size of 60nm; before preparing the nano copper alloy particles, the particles of the above CW-Cu-Zn product below 20nm and above 100nm are screened out.
[0068] Granule 1: The preparation steps are as follows:
[0069] Step 1: sodium alginate, hydroxypropyltrimethylammonium chloride chitosan, nano copper-zinc alloy, modified attapulgite 1 and water are added into a container, heated to 52° C. and stirred at 80 rpm for 5 hours to obtain a mixture;
[0070] Among them, the mass ratio of sodium alginate and hydroxypropyltrimethylammonium chloride chitosan is 0.8:1, the mass ratio of water to modified attapulgite 1 is 15:1, the mass ratio of the total mass of sodium alginate and hydroxypropyltrimethylammonium chloride chitosan to the nano-copper-zinc alloy is 1.5:1, and the mass ratio of modified attapulgite 1 to the nano-copper-zinc alloy is 30:1;
[0071] Step 2: Filter the mixture using a nanofiltration membrane with a pore size of 2 nanometers, calcine the filtered solid material at 780° C. for 2 hours, ball mill and sieve to select particles with a particle size between 10 and 100 microns to obtain intermediate material particles;
[0072] Step 3: Mix the intermediate material particles and potassium permanganate with a particle size of 10-100 microns in a mass ratio of 35:1 to obtain the nano copper alloy particles.
[0073] Granule 2: The preparation steps are as follows:
[0074] Step 1: sodium alginate, hydroxypropyltrimethylammonium chloride chitosan, nano copper-zinc alloy, modified attapulgite 2 and water are added into a container, heated to 50° C. and stirred at 80 rpm for 4.5 hours to obtain a mixture;
[0075] Among them, the mass ratio of sodium alginate and hydroxypropyltrimethylammonium chloride chitosan is 0.5:1, the mass ratio of water to modified attapulgite 2 is 16.5:1, the mass ratio of the total mass of sodium alginate and hydroxypropyltrimethylammonium chloride chitosan to the nano-copper-zinc alloy is 1.8:1, and the mass ratio of modified attapulgite 2 to the nano-copper-zinc alloy is 29.5:1;
[0076] Step 2: Filter the mixture using a nanofiltration membrane with a pore size of 2 nanometers, calcine the filtered solid material at 720° C. for 2.5 hours, ball mill and sieve to select particles with a particle size between 10 and 100 microns to obtain intermediate material particles;
[0077] Step 3: Mix the intermediate material particles and potassium permanganate with a particle size of 10-100 microns in a mass ratio of 35:1 to obtain the nano copper alloy particles.
[0078] Granule 3: The difference from Granule 1 is: Step 1: Add hydroxypropyl trimethyl ammonium chloride chitosan, nano copper-zinc alloy, modified attapulgite 1 and water into a container, heat to 52°C and stir at 80 rpm for 5 hours to obtain a mixture; wherein the mass ratio of water to modified attapulgite 1 is 15:1, the mass ratio of hydroxypropyl trimethyl ammonium chloride chitosan to nano copper-zinc alloy is 1.5:1, and the mass ratio of modified attapulgite 1 to nano copper-zinc alloy is 30:1. The rest is the same as Granule 1.
[0079] Granule 4: The difference from Granule 1 is: Step 1: Sodium alginate, nano copper-zinc alloy, modified attapulgite 1 and water are added to a container, heated to 52°C and stirred at 80 rpm for 5 hours to obtain a mixture; wherein the mass ratio of water to modified attapulgite 1 is 15:1, the mass ratio of sodium alginate to nano copper-zinc alloy is 1.5:1, and the mass ratio of modified attapulgite 1 to nano copper-zinc alloy is 30:1. The rest is the same as Granule 1.
[0080] Granule 5: The difference from Granule 1 is that the mass ratio of sodium alginate and hydroxypropyltrimethylammonium chloride chitosan is 0.1:1, and the rest is the same as Granule 1.
[0081] Granule 6: The difference from Granule 1 is that the mass ratio of sodium alginate and hydroxypropyltrimethylammonium chloride chitosan is 2:1, and the rest is the same as Granule 1.
[0082] Granule 7: The difference from Granule 1 is that the filtered solid material is calcined at 500°C for 2.5 hours. The other conditions are the same as those of Granule 1.
[0083] Granule 8: The difference from Granule 1 is that the filtered solid material is calcined at 1100° C. for 2.5 hours. The other conditions are the same as those of Granule 1.
[0084] Granule 9: The difference from Granule 1 is that modified attapulgite 3 is used to replace modified attapulgite 1, and the rest is the same as Granule 1.
[0085] Granule 10: The difference from Granule 1 is that modified attapulgite 4 is used to replace modified attapulgite 1, and the rest is the same as Granule 1.
[0086] Granule 11: The difference from Granule 1 is that modified attapulgite 5 is used to replace modified attapulgite 1, and the rest is the same as Granule 1.
[0087] Granule 12: The difference from Granule 1 is that modified attapulgite 6 is used to replace modified attapulgite 1, and the rest is the same as Granule 1.
[0088] 3. Performance Test
[0089] The above particles were used to treat the newly produced liquor, and then the changes in the content of acetaldehyde, acetal, ethyl acetate and ethyl lactate in the treated liquor were tested, and the taste of the liquor was evaluated. The specific test steps are as follows:
[0090] Take the newly produced liquor, mix the above particles with the newly produced liquor at an amount of 2% of the mass of the newly produced liquor, stir for 15 days, and then filter with a nanofiltration membrane with a pore size of 2 nanometers. The filtrate is treated with food-grade cation exchange resin ZGC108DQ (Zhejiang Zhengguang Industrial Co., Ltd.) to remove manganese and impurities. Test the content of acetaldehyde, acetal, ethyl acetate and ethyl lactate in the newly produced liquor and the liquor after the above treatment, and evaluate the taste of the liquor. The content of substances in the liquor before and after the treatment and the taste evaluation results are shown in Table 1. The changes in the content of substances in the treated liquor compared with the newly produced liquor are shown in Table 2.
[0091] Table 1: Content of substances in wine before and after treatment and taste evaluation
[0092]
[0093] Table 2: Changes in the content of substances in the treated liquor compared to the newly produced liquor
[0094]
[0095] The invention uses attapulgite to be treated with hydrogen peroxide and hydrochloric acid, and then calcined to obtain modified attapulgite; then the modified attapulgite is treated with sodium alginate and hydroxypropyltrimethylammonium chloride chitosan to obtain nano copper-zinc alloy, and then calcined to obtain nano copper alloy particles. The particles are used to treat newly produced liquor, and have a good aging and alcoholization effect on the newly produced liquor.
[0096] After the nano copper alloy particles of the present invention are used to treat new liquor, the acetaldehyde content can be reduced by 31.25%, making the liquor more beneficial to human health and reducing the adverse taste caused by acetaldehyde to a large extent.
[0097] After the nano copper alloy particles of the present invention are used to treat new wine, the proportion of acetal content can be reduced to as low as 4.82%.
[0098] After the nano copper alloy particles of the present invention are used to treat new wine, the contents of ethyl acetate and ethyl lactate can be increased by 8.34% and 11.27% respectively. It is speculated that the attapulgite modification process of the present invention makes the modified attapulgite have a better adsorption effect on small molecules in liquor, such as alcohol, aldehyde, acid and impurities, and reduces the content of acetaldehyde, an unfavorable component; and can better adsorb the nano copper alloy so that it can be better loaded in the attapulgite, thereby exerting a better catalytic aging effect and making the ester content higher.
[0099] Through the treatment effects of particles 1, 3-4, it can be obtained that in the preparation system of the present invention, the combination of sodium alginate and hydroxypropyl trimethyl ammonium chloride chitosan is better than the use of one of them, and the two have a mutually reinforcing relationship in promoting the alcoholization effect of new wine. The reason for this may be that the combination of the two can make the nano copper-zinc alloy in step 1 better dispersed in the mixture system, thereby enhancing the nano copper alloy load in the modified attapulgite, so as to better play the catalytic aging effect; and the two are calcined at 700-850 ° C in step 2 to make sodium alginate and hydroxypropyl trimethyl ammonium chloride chitosan ash so as to separate from the pores and surface of the attapulgite, so as to achieve the effect of reducing or increasing the porosity of the attapulgite. When the ratio of the two is in the range of 0.5-1:1, the obtained particles have a better effect on treating new wine, which can be specifically obtained from the test results of particles 1, 5-6.
[0100] Through the treatment effects of particles 1, 9-10, it can be seen that when preparing modified attapulgite, the use of hydrogen peroxide and hydrochloric acid solution can increase the treatment effect of the particles on new wine, increase the taste of the wine and reduce the content of unfavorable components. The test results of particles 9-10 show that the combination of hydrochloric acid solution with a concentration of 20-30wt% and hydrogen peroxide with a concentration of 5-10wt% can synergistically promote the effect of particles in treating new wine, increase the ester content in the wine and reduce the acetaldehyde content, and improve the aroma of the wine. The effect produced by low-concentration hydrochloric acid solution and hydrogen peroxide is much worse than the effect of particles obtained by treating attapulgite with hydrochloric acid solution with a concentration of 20-30wt% and hydrogen peroxide with a concentration of 5-10wt%.
[0101] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. The application of nano copper alloy particles in aging wine is characterized by: The preparation method of the nano copper alloy particles is as follows: step 1: adding sodium alginate, hydroxypropyl trimethyl ammonium chloride chitosan, nano copper-zinc alloy, modified attapulgite and water into a container, heating and stirring to obtain a mixture; step 2: filtering, calcining the filtered solid material, ball milling, screening, and obtaining intermediate material particles; step 3: mixing the intermediate material particles with potassium permanganate to obtain the nano copper alloy particles; in the step 1, the mass ratio of sodium alginate to hydroxypropyl trimethyl ammonium chloride chitosan is 0.5-1:1; in the step 2, the calcination temperature is 700-850°C, and the time is 1.5-3 hours; In the step 1, the preparation method of modified attapulgite is as follows: S1: stirring attapulgite with water, acid solution and hydrogen peroxide to obtain a stirred material; S2: filtering the stirred material, filtering the solids, calcining, grinding and screening to obtain the modified attapulgite; the acid solution is a hydrochloric acid solution with a mass concentration of 20-30%, and the concentration of the hydrogen peroxide is 5-10wt%; wherein the nano copper-zinc alloy is a product of Shanghai Chaowei Nanotechnology Co., Ltd. with a model of CW-Cu-Zn, and an average particle size of 60nm; before preparing the nano copper alloy particles, the particles below 20nm and above 100nm in the CW-Cu-Zn product are screened out; In the step 1, the mass ratio of the total mass of sodium alginate and hydroxypropyltrimethylammonium chloride chitosan to the nano-copper-zinc alloy is 1-2:1; in the step 1, the mass ratio of modified attapulgite to the nano-copper-zinc alloy is 10-100:1; in the step 2, the particle size obtained by screening is 10-100 microns; in the step 3, the mass ratio of the intermediate material particles to potassium permanganate is 10-100:
1.
2. The use according to claim 1, characterized in that The application comprises the steps of mixing nano copper alloy particles with newly prepared wine and then filtering with nano membrane.